Experimental research on remaining oil distribution and recovery performances after nano-micron polymer particles injection by direct visualization. (15th January 2018) - Yue, Ming; Zhu, Weiyao; Han, Hongyan; Song, Hongqing; Long, Yunqian; Lou, Yu
Highlights: The visualization tests by nano-micron polymer particles flooding is implemented. Four mechanism: fluid diversion, pressure fluctuation, profile control, exfoliation. Four types of remaining oil: cluster, columnar, membrane, blind-end are established. The best type of remaining oil for recovery ratio improvement is cluster up to 8.93%. Abstract: Assessments of oil recovery water flooding processes have shown that 70% of the remaining oil remains underground. Therefore, studies have focused on the formation and distribution of this remaining microscopic oil to enhance oil recovery. In this study, a microscopic visualized physical model, under high-temperature and -pressure conditions, was used for reservoir pore network similarly. Thus, these images enable observation and analysis of the formations and micro distributions of the remaining oil in water-driven and nano-micron polymer flooding conditions to better understand the morphology and migration characteristics. The displacement mechanism was studied for the nano-micron polymer particles flooding. By comparing the distributions of the different types of microscopic remaining oil, the characteristics of the multiphase fluid transports in porous media were described. The distributions of the remaining oil ratio of the models during the different flooding stages were obtained quantitatively by using gray image-processing technology. The experimental results showed that the recovery efficiency under the nano-micron polymer dispersion state could be enhanced by approximately 14.7% compared to that of the water flooding. Different effects were evident for the four types of remaining oil following the nano-micron polymer particles flooding: 1) clusters; 2) columnar; 3) membrane; and 4) blind-end. The remaining oil after water flooding was distributed mainly in the unswept water areas, surfaces of the oil-wet rock, dead-end pores, small pores or low permeability layers, and partially blocked pores. The remaining oil distribution after the polymer flooding process was mainly in the sealed and small pores, and the oil adsorption on the surface conditions of the moveable wet rock oil. The distribution of the remaining oil and the different types of remaining oil ratio after the polymer particles injection further revealed that the characteristics of the polymer particles improved the oil recovery. The polymer particles concentration and injection time on such factors and the distribution of the heterogeneous particle concentration were conducive to the expansion of the swept volume. It was determined that the nano-micron polymer flooding could efficiently improve the oil recovery of the cluster, column, and membrane types of remaining oil. Therefore, this study concludes that, if nano-micron polymer particles flooding is used to improve oil recovery efficiently, the occurrence state and distributions of the remaining oil should be considered.